2021
DOI: 10.2147/ijwh.s309096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Diseases-2019 (COVID-19) on Utilization and Outcome of Reproductive, Maternal, and Newborn Health Services at Governmental Health Facilities in South West Ethiopia, 2020: Comparative Cross-Sectional Study

Abstract: Background:In low-and middle-income countries, it is challenging to provide basic healthcare services even before the COVID-19 pandemic outbreak. The purpose of this study was to evaluate the early indirect impact of COVID-19 on the utilization of reproductive, maternal, and newborn health services at government health facilities in South West Ethiopia, and its consequences. Methods: A comparative cross-sectional study was employed. The collected data were entered into Microsoft excel 2010 and then exported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(120 citation statements)
references
References 21 publications
(34 reference statements)
4
97
1
2
Order By: Relevance
“…Of 9953 records in the initial search, 45 articles were eligible for inclusion, of which 44 were used in the quantitative synthesis 2 , 6 , 7 , 8 , 9 , 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 (Figure 1 ). Twenty‐six full‐text reports were excluded: reasons for the exclusions are provided in Appendix S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Of 9953 records in the initial search, 45 articles were eligible for inclusion, of which 44 were used in the quantitative synthesis 2 , 6 , 7 , 8 , 9 , 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 (Figure 1 ). Twenty‐six full‐text reports were excluded: reasons for the exclusions are provided in Appendix S2 .…”
Section: Resultsmentioning
confidence: 99%
“… 28 In Rwanda, the pandemic significantly affected the access to and utilization of MCH services. 29 In Ethiopia, the pandemic affected RMNCH services and maternal and perinatal outcomes 30 and increased unintended pregnancy. 31 …”
Section: Introductionmentioning
confidence: 99%
“…11,12 In a semi-pastoralist area in western Ethiopia, there was a significant reduction in mean utilization of ANC, health facility births, FP, and RI. 13 The reduction in service utilization was observed in the setting of the communities' experiences of and perceptions toward COVID-19, including misinformation, misconceptions, and doubt. As the pandemic has progressed, service utilization may further decline as fear settles in.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, a study in western Ethiopia showed a significant reduction in mean utilization of ANC, health facility birth, FP, and newborn immunization services between March-June 2019 and March-June 2020. 13 In Nepal, a qualitative study found that maternity services, immunizations, and supply of essential medicine were the most affected health services during the lockdown. Interruptions were mainly due to the closure of health services at local health care facilities, limited affordability, involvement of private health sectors during the pandemic, fears of COVID-19 transmission among health care workers and within health centers, and disruption of transportation services.…”
Section: Introductionmentioning
confidence: 99%